High-power InAs quantum-dot superluminescent diodes with offset J-shaped waveguides - Yoo, Young Chae; Han, Il Ki; Kim, Jee Hyun (KOREAN PHYSICAL SOC, 2012)
We demonstrate a superluminescent diode (SLD) that uses an offset between straight and bent regions in a J-shaped ridge waveguide. The output power is improved several times with respect to similar J-shaped SLDs without the offset. We obtain a high, continuous output power of 31 mW and wide spectral bandwidths up to 90 nm centered at about 1.1 A mu m.